Manajemen risiko sebagai kunci strategis masa depan perbankan syariah di tengah pertumbuhan dan tuntutan kepatuhan - Saputri, Wilyana Erfian (Maliki Interdisciplinary Journal, 2026)
The growth of Islamic banking in Indonesia continues to increase, supported by rising public awareness and regulation from the Otoritas Jasa Keuangan. However, this growth is accompanied by financial, operational, and Sharia compliance risks that may affect stability. This study aims to examine the role of risk management in balancing growth and compliance in Islamic banking. Using a qualitative descriptive approach through a literature review, the findings show that risk management is essential in identifying, measuring, and controlling risks, including non-performing financing and compliance risk. The integration of risk management and Sharia compliance also strengthens customer trust and competitiveness. Therefore, strengthening risk management systems, improving human resources, and enhancing internal supervision are crucial for the future sustainability of Islamic banking.